2019
DOI: 10.33549/physiolres.934298
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of miRNA-1, miRNA-29g and miRNA-133s Plasma Levels in Prostate Cancer Patients With High-Intensity Training After Androgen-Deprivation Therapy

Abstract: The randomized trials showed that the addition of training resistance program to androgen-deprivation therapy (ADT) had many beneficial effects for prostate cancer (PC) patients (significant protective effect on the volume of muscle mass) and the studies have revealed a panel of miRNAs, which are deregulate in PC and may serve as promising biomarkers of PC risk. The primary aim of our present study was to investigate the effect of exercise training to changes in body composition (muscle strength) and the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 37 publications
0
18
0
Order By: Relevance
“…Taaffe et al [50] reported similar findings, although the between-group difference did not reach statistical significance. Finally, Gazova et al [47] reported no effect of 4 months of RE on BMD. The results of the included studies are presented in Table 2.…”
Section: Independent Articlesmentioning
confidence: 97%
See 4 more Smart Citations
“…Taaffe et al [50] reported similar findings, although the between-group difference did not reach statistical significance. Finally, Gazova et al [47] reported no effect of 4 months of RE on BMD. The results of the included studies are presented in Table 2.…”
Section: Independent Articlesmentioning
confidence: 97%
“…The risk of bias analysis showed that the five independent articles published after 1 January 2017 were predominantly of a moderate to high methodological quality, with the exception of one study being classified as having a high risk of bias [47]. The results of the analysis for both the intention-to-treat effect are shown in Fig.…”
Section: Risk Of Biasmentioning
confidence: 97%
See 3 more Smart Citations